How entrepreneurs' personal characteristics affect SMEs' growth - Širec, Karin (Naše gospodarstvo, 2010)
This paper investigates differences in the personal characteristics of entrepreneurs and their impact on SMEs'' growth. The concept of entrepreneurial individuals with distinguishing characteristics is central to entrepreneurial theory, according to which we operationalized entrepreneurs through a division based on psychological and non-psychological motivation factors. For each category of the model, we describe the findings of our study, especially exposing statistically significant factors affecting SMEs'' growth. Reasonableness and the applicability of our research are legitimate for three target groups: society as a whole, policymakers and academics investigating entrepreneurial phenomena. We conclude the paper with recommendations for policy implications that stimulate growth and encourage companies'' performance/growth.
Keywords: mala podjetja; srednja podjetja; rast; razvoj; podjetništvo; podjetniki; osebnostne lastnosti; osebnostni razvoj; motivacija; motivation